A Study of Strong Noise on Human Heart Rate Changes - Lu, Ling (International Journal of Public Health and Medical Research, 2024)
Under stressful conditions, the body produces a series of biological responses, such as significant changes in heart rate, blood pressure, respiration, and glandular activity, etc. Strong noise also has an effect on physiology. In the following research, Heart rate was selected as the psychophysiological index reflecting the psychological changes of the subjects, and the psycho-emotional changes of the subjects under the stimulation of strong noise samples were analyzed laterally by measuring the results of the physiological indexes before and after the subjects' experiments. Results showed that Subjects' heart rate variability changed significantly and with similar trends under noise stimulation, and changed more as the noise loudness level increased.